Agriculture U.S.A.' television show
Producer John A. Stearns (not pictured) of the television show "Agriculture U.S.A." posing questions to three agricultural quiz contestants during a taping of the show in Burbank, Calif. Left to right are David Schaffner representing the University of California at Davis; Michael Franscioni of Cal Poly; and James O' Banion of Fresno State. Appearing on the same show was Santa Fe Railway Vice President Robert W. Walker of San Francisco who discussed the vital role of railroad transportation